Boundary layer instabilities in high and low enthalpy hypersonic facilities using high speed schlieren - Subiah, SD (2022)
This thesis presents results from the first experiments conducted in the Oxford T6 Stalker Tunnel in Reflected Shock Tunnel mode and observations on the boundary layer instabilities established over a cone model at Mach 7 and Mach 8 conditions characterised using high speed schlieren image processing techniques.